Patterns of prophylactic gastrostomy tube placement in head and neck cancer patients: A consideration of the significance of social support and practice variation. (7th February 2013) - Locher, Julie L.; Bonner, James A.; Carroll, William R.; Caudell, Jimmy J.; Allison, Jeroan J.; Kilgore, Meredith L.; Ritchie, Christine S.; Tajeu, Gabriel S.; Yuan, Ya; Roth, David L.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The purpose of this study was to examine factors associated with prophylactic placement of feeding tubes in head and neck cancer patients receiving radiation therapy as a part of treatment using multilevel models that account for patient‐, physician‐, and institution‐level sources of variation. Study Design A retrospective analysis using binary logistic regression and hierarchical linear models was run to evaluate independent predictors of prophylactic feeding tube placement. Methods Surveillance, Epidemiology, and End Results–Medicare data were used. Head and neck cancer patients diagnosed with locoregionally advanced stage disease from 2000 to 2005 were included in this study (N = 8, 306). Results Across all models, prophylactic gastrostomy tube placement was found to be more likely in patients who had cancer of the larynx or oropharynx compared with those with cancer of the nasopharynx or oral cavity; who had regional instead of local cancer; who did not receive surgery as a part of treatment, but did receive chemotherapy; and who were divorced, separated, or widowed. Additionally, although practice variation was observed to occur, its overall contribution in predicting prophylactic gastrostomy tube placement was minimal. Conclusions As health care enters an era of patient‐centered care, further investigation of the potential role of social support (or lack of social support) in influencing treatment decisions of head and neck cancer patients and providers is warranted. Level of Evidence 2b Laryngoscope, 123:1918–1925, 2013